Effect of Carbon Nanotubes on Direct Electron Transfer and Electrocatalytic Activity of Immobilized Glucose Oxidase - Liu, Yuxiang; Zhang, Jin; Cheng, Yi; Jiang, San Ping (2018)
© 2018 American Chemical Society. Carbon nanotubes (CNTs) are excellent supports for electrocatalysts because of their large surface area, excellent electronic conductivity, and high chemical and structural stability. In the present study, the activity of CNTs on direct electron transfer (DET) and on immobilized glucose oxidase (GO X ) is studied as a function of number of walls of CNTs. The results indicate that the GO X immobilized by the CNTs maintains its electrocatalytic activity toward glucose; however, the DET and electrocatalytic activity of GO X depend strongly on the number of inner tubes of CNTs. The GO X immobilized on triple-walled CNTs (TWNTs) has the highest electron-transfer rate constant, 1.22 s -1 , for DET, the highest sensitivity toward glucose detection, 66.11 ± 5.06 µA mM -1 cm -2 , and the lowest apparent Michaelis-Menten constant, 6.53 ± 0.58 mM, as compared to GO X immobilized on single-walled and multiwalled CNTs. The promotion effect of CNTs on the GO X electrocatalytic activity and DET is most likely due to the electron-tunneling effect between the outer wall and inner tubes of TWNTs. The results of this study have general implications for the fundamental understanding of the role of CNT supports in DET processes and can be used for the better design of more effective electrocatalysts for biological processes including biofuel cells and biosensors.